Treatment of Concomitant ACL and MCL Injuries: Spontaneous Healing of Complete ACL and MCL Tears - Razi, Mohammad; Soufali, Amir Payman; Ziabari, Elaheh Ziaei; Dadgostar, Haleh; Askari, Alireza; Arasteh, Peyman (The Journal of Knee Surgery, 2020)
The mainstay of treatment for anterior cruciate ligament (ACL) tear is considered to be surgery, especially when associated with medial collateral ligament (MCL) tears. We aimed to evaluate our hypothesis that some patients with concomitant ACL and MCL tears may develop spontaneous healing without surgical intervention. This study was conducted during 2013 to 2017. A total of 707 patient referred with combined ACL and MCL injuries. Patients were divided into three groups according to type of ACL and MCL management as follows: (1) group 1 as those who only had ACL reconstruction without any surgical treatment of MCL; (2) group 2 as those who had ACL reconstruction and MCL surgery (reconstruction, reefing, or both); (3) group 3 as those who showed spontaneous healing of ACL and MCL. Overall, 206 and 129 patients entered groups 1 and 2, respectively. Overall, 15 patients showed spontaneous healing of ACL and entered group 3. Skiing and soccer were the most common causes of injury within the third group, followed by traffic accidents (35.7%, 35.7% and 21.4%, respectively). All these were noncontact injuries within this groups. In group 3 only three patients had concomitant meniscal injury. Mean healing time for patient with spontaneous healing was 8.66 ± 3.41 months. All patients showed ACL tears at the proximal part of its attachment. During follow-up, all pivot shift, Lachman and MCL tests were either negative or one plus. All these individuals returned to previous physical activity. Among the total number of patients with skiing injuries presenting with concomitant ACL/MCL injuries (27 patients), five patients (18.5%) showed spontaneous healing. Valgus and external rotation injuries with dominancy of valgus force, apart from a MCL tear, may lead to proximal tear of ACL as well, and the inflammation from the torn MCL can potentiate and stimulate the healing process of ACL; thus, patient with this mechanism of injury is better followed before surgical intervention is planned as spontaneous healing may occur.
Keywords: anterior cruciate ligament; medial collateral ligament; spontaneous healing; mechanism of injury; skiing